Impact of nonpneumatic antishock garment in the management of patients with hypoperfusion due to massive postpartum hemorrhage. (16th September 2020) - Escobar, Maria Fernanda; Fernández Pérez, Paula Andrea; Carvajal, Javier Andrés; Burgos, Juan Manuel; Messa, Adriana; Echavarria, Maria Paula; Nieto, Albaro; Montes, Daniela; Miller, Suellen; Hurtado, David Felipe
Abstract: Objective: The objective of this article was to compare hemodynamic and perfusion parameters as well as the clinical outcomes in critically ill patients with postpartum hemorrhage (PPH) who received treatment with a nonpneumatic antishock garment (NASG) as part of an intervention package, with a group of patients in similar conditions who did not receive an NASG. Methods: This observational study analyzed a historic cohort of 154 patients with PPH, secondary hypovolemic shock and signs of hypoperfusion who were admitted to this institution from 2012 to 2015. Group 1 ( n = 77) was managed with NASG and Group 2 ( n = 77) received interventions other than NASG. Hypoperfusion markers and maternal outcomes were compared in both groups. Results: Of 154 patients included in the analysis, 36.4% required a total abdominal hysterectomy (TAH) to achieve hemorrhage control, 98.2% of whom belonged to Group 2 and 1.8% to Group 1 ( p = .001). The use of blood products was more common in Group 2 ( p < .001), as was the administration of vasoactive agents. The mean number of days of hospitalization at the Obstetric High Dependency Unit (OHDU) was significantly lower in Group 1 and reached a statistically significant p value. Only two cases of maternal death occurred in Group 2. Discussion: The use of NASG in the management of PPH is a cost-effective strategy for patients with severe shock and signs of hypoperfusion and is optimal in a limited-resource scenario. In this study, the use of NASG was related to better outcomes in a statistically significant manner with better results regarding maternal outcomes such as uterine preservation and decreased transfusion requirements and hospital days. Conclusions: NASG, associated with the use of uterotonic agents and other strategies for PPH control, is a safe tool that helps reduce morbimortality in critically ill patients with PPH.